Fejerverkų sukeltas trauminis chorioretinitas: klinikinis atvejis ir literatūros apžvalga - Kazlauskaitė, Greta; Misevičė, Aušrinė (Lietuvos chirurgija, 2023)
Chorioretinitis sclopetaria is a rare consequence of ocular injury caused by the forces of a high-velocity object passing very close to the globe. Injury results in a full-thickness rupture of the retina and choroid, while the sclera remains unaffected. The location of rupture affects visual recovery and final best-corrected visual acuity. Retinal detachment or non-resorbable vitreous hemorrhage may require surgical treatment, but in most cases the initial treatment is observation. Therefore, a timely and correct diagnosis of traumatic chorioretinitis is essential to avoid unwarranted surgical intervention. Although most patients have a final corrected visual acuity improvement after trauma, the visual prognosis is poor. Herein we report the case of a patient diagnosed with chorioretinitis sclopetaria after sustaining trauma by a firework. We also discuss the prevalence of chorioretinitis sclopetaria, risk factors, the pathophysiological mechanism, the main clinical findings, treatment options, and outcomes.
Keywords: trauminis chorioretinitas; fejerverkų traumos; akių traumos